Positional relationship between several performance tests and physical profile of Brazilian football athletes - Gabriel Andrade Paz; Marianna de Freitas Maia; Haroldo Sant'Ana; Humberto Miranda; Juliana Brandão Pinto de Castro; Vicente Pinheiro Lima (Universidade Estadual de Maringá, 2019)
The purpose of this study was to investigate the association between anthropometric (height and weight) and physical parameters in Brazilian football athletes and to determine if the relationship between various anaerobic indices of running anaerobic sprint test (RAST) and physical performance are dependent upon position. The present study is an observational, randomized cross-sectional research, where thirty-eight players (24.7 ± 3.9 years) performed a series of tests that consisted of physical fitness (horizontal jump, abdominal curl, push up, 10, 20 and 30 m sprint speed), anthropometric and RAST assessments. The players were classified into three groups: skill players (n = 14), big skill players (n = 10), and linemen (n = 14). One-way ANOVA followed by Bonferroni test presented no difference between groups for anthropometric, horizontal jump, push up, T agility, 10, 20, and 30 m sprint speed tests and all anaerobic indices computed (p > 0.05). However, higher abdominal curl performance was noted under skill player versus big skill player group (p = 0.045). In big skill players group, the relationship between 10, 20 and 30 m sprint speed and muscle power reduction index was great. In conclusion, the results of the current study indicated that only agility and sprint tests presented an association with the anaerobic performance for all group analyzed.